COVID-19 Traveler Policy in Migrant Worker: How it Helped Shape Distinct Clusters During the Early Phases of the Pandemic - Saktivi Harkitasari; Richard Christian Suteja; Giovanca Verentzia Purnama; I Komang Hotra Adiputra; Jerry; I Gede Purna Weisnawa; Cokorda Agung Wahyu Purnamasidhi (Warmadewa University, 2023)
Though COVID-19 caught healthcare authorities worldwide off guard, several countries successfully dampened the morbidity and mortality curve by imposing strict biosecurity protocols. We would like to observe the effect of healthcare policies enforced in correlation to the formation of new clusters during early phases of the pandemic, thereby providing statistical justification for laws enforced by authorities. With access to medical records from Udayana University Hospital, a tertiary COVID-19 referral health center, we then observe epidemiological data of patients admitted and their admission date in correlation to dates where major changes in national COVID-19 protocols were established. We found a double distinctive curve that is mainly made of two distinct demographic groups: migrant workers and private employees. We found that during March 2020, when strict travel protocols are yet to be imposed, the viral introduction was mostly carried by returning migrant workers. Sporadic cases emerged, though soon vanishing due to the enforcement of quarantine protocols. Subsequently, in June 2020, a work-from-office setting was adopted, where some offices perform at a capacity higher than allowed. This incites the formation of new office-linked clusters. After this period, no recognizable pattern found due to massive local transmission affecting all layers of society. However, it can be concluded that COVID-19 law does shape the curve, and strict protocols may end the pandemic sooner. Keywords: COVID-19, Migrant Workers, Health Policy, Private Employee